ANALISIS STRATEGI PEMASARAN UMKM SEMBAKO DI PASAR TRADISIONAL BERSEHATI KOTA MANADO - Jeysri Maarontong; Silvya L. Mandey; Christoffel M. O. Mintardjo (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2026)
This study aims to analyze the marketing strategies of grocery SMEs at Bersehati Traditional Market in Manado City based on the 7P marketing mix and relationship marketing approaches. This research was motivated by increasing business competition, the development of modern retail markets, changes in consumer behavior, and the importance of social relationships in traditional market trading activities. The study employed a descriptive qualitative approach to obtain an in-depth understanding of the marketing strategies implemented by grocery SMEs. The research was conducted at Bersehati Traditional Market in Manado City with 20 informants consisting of 5 main and 15 supporting informants. Data collection techniques included observation, interviews, and documentation. Data analysis used the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and drawing conclusions. Data validity was ensured through source triangulation, technique triangulation, and time triangulation.The results showed that the marketing strategies of grocery SMEs at Bersehati Traditional Market are still dominated by traditional marketing approaches based on social relationships, service quality, product quality, and customer closeness. The aspects of product, price, people, and relationship marketing were found to be important factors in maintaining customer loyalty and business sustainability. In addition, interpersonal relationships, direct communication, and customer trust significantly influence SME marketing activities in traditional markets.This study concludes that the implementation of the 7P marketing mix in grocery SMEs is influenced not only by economic aspects but also by social dimensions and interpersonal relationships between sellers and customers. Therefore, strengthening relationship-based marketing strategies is an important factor in improving the competitiveness and sustainability of grocery SMEs in traditional markets.